2015
DOI: 10.1007/s10877-015-9723-6
|View full text |Cite
|
Sign up to set email alerts
|

Automated gas control with the Maquet FLOW-i

Abstract: The FLOW-i anesthesia machine (Maquet, Solna, Sweden) can be equipped with automated gas control (AGC), an automated low flow tool with target control of the inspired oxygen concentration (FIO2) and end-expired concentration (FA) of a potent inhaled anesthetic. We examined the performance and quantitative aspects of the AGC. After IRB approval and individual informed consent, anesthesia in 24 ASA I-II patients undergoing abdominal or gynecological surgery was maintained with sevoflurane in O2/air with a target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 11 publications
0
16
0
1
Order By: Relevance
“…Because of a lack in theoretical and clinical data to characterize the alterations of pharmacokinetics of volatile anesthetics in obese patients, these systems may have errors in their prediction. End-tidal control delivery machines like Zeus® (Dräger Medical), Aisys EtControl™ (GE Healthcare, Madison, WI, USA) and the FLOW-i (Maquet, Getinge AB, Getinge, Sweden) adjust the vaporizer output and fresh gas flow (FGF) automatically to reach and maintain a previously set end-tidal volatile anesthetics' concentration [21][22][23] and will be less or not-at-all affected by model errors.…”
Section: Introductionmentioning
confidence: 99%
“…Because of a lack in theoretical and clinical data to characterize the alterations of pharmacokinetics of volatile anesthetics in obese patients, these systems may have errors in their prediction. End-tidal control delivery machines like Zeus® (Dräger Medical), Aisys EtControl™ (GE Healthcare, Madison, WI, USA) and the FLOW-i (Maquet, Getinge AB, Getinge, Sweden) adjust the vaporizer output and fresh gas flow (FGF) automatically to reach and maintain a previously set end-tidal volatile anesthetics' concentration [21][22][23] and will be less or not-at-all affected by model errors.…”
Section: Introductionmentioning
confidence: 99%
“…The software aims to have both financial and environmental benefits; however, it can come at an additional cost from the manufacturer. The benefits have been documented in the adult setting but there is no quantification of the benefit in pediatric anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…One explanation could be the set-up of speed 6 in TA B L E 2 Desflurane consumption (mL liquid) after 9, 30 and 60 min our study as Carette et al observed that the volatile anaesthetic consumption in Flow-I AGC is higher for speed 6 compared to speed 2. 17 It is unclear whether the chosen speed for the Flow-I AGC had an impact on our results.…”
Section: Discussionmentioning
confidence: 87%
“…14 However, since the introduction of automated gas control delivery systems only a few studies have investigated functionality and effects on volatile anaesthetic consumption. [14][15][16][17][18][19][20] The aim of this study was to compare the consumption of desflurane delivered with and without the use of automated gas control (AGC) Flow-I or end-tidal gas control Aisys gas control delivery systems. We also compared volatile anaesthetic consumption between the two different automated anaesthetic gas control systems used in the study, the time it took to reach a minimum alveolar concentration of 0.7 and the time to reach a FGF of 0.5 L/min.…”
Section: Introductionmentioning
confidence: 99%